Rational Palintropy, or: The Productive Tension of the History of Ideas - Piergiacomi, Enrico (Annali di studi religiosi, 2023)
This is a short paper that spells out the sources of inspiration of my work as a historian of philosophy, namely a non-metaphysical version of Heraclitus' theory of the unity of opposites, and aims to clarify the key ideas of this methodology through four case-studies that are either at an advanced or early stage. I will summarize my investigation into the following philosophical traditions, or unities of (apparent?) opposites: (A) atomistic theology (= unity of materialism and spiritualism); (B) religious hedonism (= unity of hedonism and religion); (C) the scientific poem (= unity of science and poetry); (4) rational theories on performative arts (= unity of reason and performance).